Calixarene-Based Supramolecular Sensor Array for Pesticide Discrimination - Chen, Yeye; Tian, Jia-Hong; Tian, Han-Wen; Ma, Rong; Wang, Ze-Han; Pan, Yu-Chen; Hu, Xin-Yue; Guo, Dong-Sheng (Sensors (Basel, Switzerland), 2024)
The identification and detection of pesticides is crucial to protecting both the environment and human health. However, it can be challenging to conveniently and rapidly differentiate between different types of pesticides. We developed a supramolecular fluorescent sensor array, in which calixarenes with broad-spectrum encapsulation capacity served as recognition receptors. The sensor array exhibits distinct fluorescence change patterns for seven tested pesticides, encompassing herbicides, insecticides, and fungicides. With a reaction time of just three minutes, the sensor array proves to be a rapid and efficient tool for the discrimination of pesticides. Furthermore, this supramolecular sensing approach can be easily extended to enable real-time and on-site visual detection of varying concentrations of imazalil using a smartphone with a color scanning application. This work not only provides a simple and effective method for pesticide identification and quantification, but also offers a versatile and advantageous platform for the recognition of other analytes in relevant fields.